Surface modifications of titanium based dental implant to accelerate osseointegration process - Rita Harianti Ladong; Irfan Dammar; Eri Hendra Jubhari (Indonesia Prosthodontic Association, 2023)
Dental implants is a prosthesis that is invasively implanted in the patient’s to replace missing teeth. Osseointegra-gration is the process where structural and functional relationships take place between bone and embedded dental implant surfaces. Unfortunately, titanium based dental implants show lack of osseointegration. Therefore, dental im-plant modifications could be one way to overcome this limitation. This article intensively reviews several surface modification methods to accelerate the osseointegration process on titanium dental implants. A literature review presented in this article. It is concluded that implant surface modification with other materials could accelerate the osseointegration process. Otherwise, modification of surface implants such as physical, chemical and biological mo-dification are discussed.